Reading the canon: literary history in the 21st century - Löffler, Philipp (American studies, 2017)
Cover -- Title Page -- Copyright -- TABLE OF CONTENTS -- ACKNOWLEDGMENTS -- PHILIPP LÖFFLER: Introduction: The Practice of Reading and the Need for Literary Value -- I PERIODIZATION, PRESTIGE, GENRE -- CLEMENS SPAHR: Literary History and the Problem of Periodization -- GÜNTER LEYPOLDT: Singularity and the Literary Market -- MICHAEL BASSELER: Literary Canons and the Dynamics of Generic Change -- II CLASSICS IN THE CLASSROOM -- PETER PAUL SCHNIERER: Shakespeare's Complete Works: Canonization, Completion and Collection in the Twenty-First Century -- JOHANNES VÖLZ: The Uses of Emerson: Transcendentalism, Transnationalism, and the New Americanists -- HEIKO JAKUBZIK: Edgar Allan Poe and the Rise of Detective Fiction -- SASCHA PÖHLMANN: Canon Fodder: Thomas Pynchon, Unpopular Culture, and the Invention of Postmodernism -- III IN THE NAME OF DIVERSITY -- FRANZISKA SCHMID: Sherman Alexie and the Uses of Native American Literature -- KATHARINA GERUND: Contested Canons? Toni Morrison and the Nobel Prize in Germany -- CAROLINE LUSIN: Canon and Carnival: Challenging Hierarchies in Zadie Smith's ‚NW' (2012) -- JAN RUPP: New Canons for the Classroom: Teaching Black British Writing -- DIRK WIEMANN: The Great Unread: Indian Writing in English and its Shadow Canons -- IV LOST FIGURES, UNLIKELY REVIVALS, NEWCOMERS -- STEFANIE SCHÄFER: John Neal's ‚Brother Jonathan' and the Problem of American Romanticism -- KARIN HÖPKER: Only in the Chattel Records-Obscurity, Historiography, and Frederick Douglass's ‚The Heroic Slave' -- TIM SOMMER: Charismatic Authorship: Walter Scott, William Wordsworth, and the Nineteenth-Century Construction of Romantic Canonicity -- SOPHIE SPIELER: No Longer the 'Text-Book' of any Generation: ‚Stover at Yale' and the Non-Canonical
Keywords: Aufsatzsammlung; Gattungstheorie; Periodisierung; Kanon; Literatur; USA